Legal Certainty In Financial Disputes Case Resolution Progressive Legal Perspective - Sembiring, Ferdinand; Saragih, Yasmirah Mandasari (Journal of Progressive Law and Legal Studies, 2024)
Pure Legal Theory (The Pure Theory of Law) is a positive legal theory. However, it does not discuss positive Law that applies in a particular legal system; it only discusses general legal theory. Hans Kelsen's presentation of Pure Legal Theory aims to explain the nature of Law and methods of making Law rather than explaining what the Law should be or the best way for Law to be created. This writing uses descriptive legal research, in which the author uses a normative juridical research type using the Library Research data collection method. This research aims to determine how the legal certainty and protection of the parties in mediating the resolution of Sharia financial disputes, a comparison of progressive legal analysis of Hans Kelsen and Satjipto Raharjo's legal theory in resolving Sharia financial disputes. Based on the research and discussion results, a picture is obtained that legal certainty (rechtssicherheit) Legal certainty is the certainty of laws or regulations; all kinds of methods, methods, and so on must be based on laws or regulations. Within legal certainty, there are positive laws and written laws. Normative legal certainty is when a regulation that regulates it clearly and logically is created and promulgated. Progressive Law wants to return the Law to the right track (on the right track). For this reason, Satjipto Rahardjo thinks that legal breakthroughs are needed (legal breakthroughs, not legal breaking) in law formation and enforcement.